Examination of Emotional Eating Levels According to the Exercise Status of Students in the Faculty of Sports Sciences - Mine Turğut,; Taner Bozkuş,; Yusuf Burak Yamaner, (Journal of Educational Issues, 2024)
This study aimed to examine the emotional eating levels of students studying at the faculty of sports sciences according to their exercise status. The screening model was used in our research. After the detailed information about the scale form was given to the participants, a total of 125 students, 66 male, and 59 female participants, participated on a voluntary basis. In addition to the personal information form prepared by the researcher, the Emotional Eating Scale (EES) was used to collect the data. SPSS 22.0 package program was used in the analysis of the obtained data. It was determined that 52.8% of the participants included in the study were male and 47.2% were female, 79.2% of these participants did exercise, and 20.8% did not. In the study, it was found that male participants had a higher sense of guilt when they consumed forbidden foods than female participants; We can say that the desire to eat of those who did not exercise was more dominant than those who did not exercise. As a result, it would not be wrong to say that exercise has positive effects on the emotional eating status of the participants. Moreover, it has been observed that individuals who exercise are more likely to control their eating status than those who do not exercise. In this context, it can be said that exercise has positive effects in terms of controlling the emotional eating status of individuals.